Nutritional Composition, Antioxidant Activity And Anticarcinogenic Effect Of Typhonium Flagelliforme (Nicholson 1029) Extract In Rat - Karuppiah, Thilakavathy (2000)
Typhonium flagelliforme from the family Araceae is locally known as rodent tuber. It is being used traditionally in Malaysia to treat cancer. The major aim of this study was to investigate the effect of Typhonium flagelliforme crude extract on hepatocarcinogenesis in rats induced by diethylnitrosamine (DEN) and 2- acetylaminofluorene (AAF). Besides the in vivo study, the plant's nutrient and non-nutrient composition, and its antioxidant activity were also determined. Typhonium flagelliforme has carbohydrate (0.5% in leaves-stalks and 27.5% in tubers-roots) as its main constituent. It has high content of vitamin C (106.5 mg/100g in leaves-stalks and 11.6 mg/100g in tubers-roots) and potassium (1276.8 mg/100g in leaves-stalks and 534 mg/100g in tubers-roots). Alkaloid (0.4 mg/100g in leaves-stalks and 0.9 mg/100g in tubers-roots) and catechin (1.5% in leaves-stalks and 0.7% in tubers-roots) were found in this plant. The phytochemicals of Typhonium flagelliforme showed a greater antioxidant activity than vitamin E.